2020
DOI: 10.1021/acs.jafc.0c01884
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Up- and Downregulation of Metabolites and Mitochondrial Content on pH and Color of the Longissimus Muscle from Normal-pH and Dark-Cutting Beef

Abstract: Limited knowledge is currently available on the biochemical basis for the development of dark-cutting beef. The objective of this research was to determine the metabolite profile and mitochondrial content differences between normal-pH and dark-cutting beef. A gas chromatography–mass spectrometer-based nontargeted metabolomic approach indicated downregulation of glycolytic metabolites, including glucose-1- and 6-phosphate and upregulation of tricarboxylic substrates such as malic and fumaric acids occurred in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Therefore, the richer Leu and Ile in the meat from pasture-fed goats may be the key reason for the better flavor. In addition, pasture-fed has been proved to have a positive impact on the image and nutrition of goat meat [31], and flesh color is closely related to pH [32]. The color of pasture-fed meat is commonly deeper for a high content of myoglobin and the content of intramuscular fat is lower, which were also proven in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the richer Leu and Ile in the meat from pasture-fed goats may be the key reason for the better flavor. In addition, pasture-fed has been proved to have a positive impact on the image and nutrition of goat meat [31], and flesh color is closely related to pH [32]. The color of pasture-fed meat is commonly deeper for a high content of myoglobin and the content of intramuscular fat is lower, which were also proven in our study.…”
Section: Discussionsupporting
confidence: 81%
“…It was previously reported that respiration machinery has an enhanced functionality in high pHu muscles. 17 , 18 , 24 , 26 As a result, increased oxygen consumption would favor its transportation by specific proteins such as HBB, explaining its overabundance in the high pHu sample ( Table 1 ). In contrast, the iron transportation TF protein was less abundant in this assayed meat group.…”
Section: Results and Discussionmentioning
confidence: 99%
“…One study related to the biochemical changes and their impact on meat color was undertaken by Ramanathan et al [115]. Their goal was to determine the differences in metabolite profile and mitochondrial content between normal-pH and dark-cutting beef.…”
Section: Foodomics As a Standard For Safety And Quality Assessmentmentioning
confidence: 99%
“…Additionally, darkcutting beef had greater mitochondrial content and higher levels of neurotransmitters such as 4-aminobutryic acid and succinate semialdehyde. The authors speculated that the mitochondrial content and downregulation of metabolites involved in glycolytic pathways resulting in lower lactic acid formation during anaerobic metabolism would result in a high-pH of dark-cutting beef [115].…”
Section: Foodomics As a Standard For Safety And Quality Assessmentmentioning
confidence: 99%